Efeito crônico do treinamento de força com restrição de fluxo sanguíneo no desempenho da função cognitiva e saúde mental de mulheres: um estudo clínico randomizado e controlado - Brasiliano, Marlon Madeiro (2021)
Human aging is a natural process accompanied by several morphological, functional and cognitive changes. Advancing age causes a consequent increase in the incidence of neurodegenerative diseases, anxiety and depression, contributing to the decline in cognitive performance. Prevention strategies through physical exercise, especially strength training, are indicated to improve aspects of cognitive function and mental health. The aim of the study was to analyze the chronic effect of strength training with restricted blood flow (BFR) on the performance of cognitive function and mental health in women. For this, 30 cognitively healthy women (65±3 years) participated in a randomized and controlled clinical study, with sixteen weeks of intervention on non-consecutive days. Participants were distributed according to age and muscle strength levels into three groups: 1) strength training with blood flow restriction (STBFR: n = 10); 2) strength training with low load (STLL: n = 10); and 3) strength training with moderate load (STML: n = 10). The exercises (bicep curl, bench press, squat and leg press 45º) were performed 3x a week at different intensities (15RM and 30RM) and equal volume (3x10 repetitions). Before and after the experiments, neuropsychological assessment tests were performed, considering the variables: cognitive function ([global - Mini Mental State Examination (MMSE), executive function - Digit Span Forward and Backward, Stroop test, Trial Making Test AB (TMT) ), phonological and semantic verbal fluency] mental health: (Beck depression inventory (BIA) and state-trait anxiety inventory (STAI) For statistical analysis, the Shapiro Wilk test was used to verify the normality of the data and Estimated Equations Generalized (EEG) for possible changes in the variables. The results showed that, in the EEG analysis, no differences were observed (P VALUE) between the training groups after 16 weeks, but a significant effect on time was observed in the cognitive function variables within from the group (pre to post) in the STLL group: digit span = 95% CI: 0.22; 4.18; STML: phonological verbal fluency test = 95% CI: -7.58; -0.28, and in mental health in the STBFR group: depression = 95% CI: 0.11; 4.68. In conclusion: performing strength training with blood flow restriction for 16 weeks does not improve cognitive performance, but it is able to reduce depression levels in healthy elderly women.